Soil chemical properties of recovered areas after gravel extraction in the Amazon Region (Research, Society and Development, 2021)
The Amazon region contributes significantly to the Brazilian mineral sector. However, there has been an increase in areas degraded by mining. Therefore, the objective of the research was to evaluate the effect of the use of revegetation on the soil chemical properties in an area under gravel extraction in the Amazon region. The experiment was carried out in a gravel mining area in Capitão Poço - PA. The experimental design used was in randomized blocks, in subdivided plots. The plots consisted of two treatments: liming + scarification and without liming and without scarification. The subplots were composed of five treatments: 1) planting seedlings of seven species + 500 kg of litter; 2) seedlings of seven species + 50 g plant-1 of NPK + 200 g plant-1 of poultry manure; 3) seedlings of seven species + 50 g plant-1 of NPK + 200 g plant-1 of poultry manure + cultivation of two cowpea lines between the seven species lines; 4) planting seedlings of seven species + 50 g plant-1 of NPK + 200 g plant-1 of poultry manure + 500 kg de topsoil and 5) natural regeneration. In general, MOS, P and K levels in the built soil were lower compared to the values obtained in the secondary forest area. In addition, there was a reduction in Al and Na levels in the constructed soils. Thus, the use of the revegetation technique proved to be promising, however, long-term follow-up is necessary.